An Application of the t-Extension of the p-Fibonacci Pascal Matrix in Coding Theory - Elahe Mehraban; Mansour Hashemi (Advances in Mathematical Physics)
We consider the t-extension of the p-Fibonacci Pascal matrix. First, we study the k-th power of the t-extension of the p-Fibonacci lower and upper triangular Pascal matrix. Then, we obtain a new code which is named the t-extension of the p-Fibonacci Pascal matrix coding/decoding by using them.